Intonation and Intensity of President Joko Widodo's Speech - Erwina, Emmy; Alvy Mawaddah; Wardana, Muhammad Kiki (International Journal of Culture and Art Studies, 2025)
This study aims to investigate the prosody of speech by the head of state related to the answer to the question that has recently gone viral and trending is President Jokowi's speech answer to the question on YouTube, with the title "Why the Capital City Not Move to Papua?". The head of state of the Republic of Indonesia (Joko Widodo) used data in the form of speech related to the conversation.  The utterances were obtained from a video titled "Why the Capital City Did Not Move to Papua? Moreover, it is downloaded from YouTube. Then, the data is selected from several sentences President Joko Widodo spoke. The voice data will be extracted and coded at the analysis stage using Praat 6.0.54 (1). This research was conducted because, until now, the study of acoustic phonetics has rarely been done. On the other hand, phonetic descriptions, especially acoustic phonetic descriptions, namely the intonation and intensity of President JokoWidodo's speech, are important to study. The purpose of this study is to physically document sound, preservation, teaching, and language dignity in the midst of the symptoms of language shift. This study is an effort that is in line with the scientific aspects of phonetics and maintaining language heritage in terms of speech. This study's results prove differences in acoustic values in the measurement results of the data "Jokowi's Answer Asked by Elementary School Children Why the Capital City is Not in Papua" on the VIVA.CO.ID YouTube account. All acoustic features were measured, namely frequency, duration, pressure, and intensity. From the analysis results, it can be concluded that the resulting tone contour shows two patterns: the rising and descending patterns. The rising pattern at the end of the utterance indicates that the utterance is unfinished, while the falling pattern at the end explains that the utterance's intonation is final. In addition, there are many increases in frequency and intensity in the data, where the increase mostly occurs when Mr. Jokowi mentions the words "Papua," "Aceh," "Sabang," "Marauke," "Capital," "North," "South," "Gitu," and "Yes."